A Randomized Trial Evaluating the Prophylactic Activity of DSM265 Against Preerythrocytic Plasmodium falciparum Infection During Controlled Human Malarial Infection by Mosquito Bites and Direct Venous Inoculation. (5th December 2017) - Murphy, Sean C; Duke, Elizabeth R; Shipman, Kelly J; Jensen, Ryan L; Fong, Youyi; Ferguson, Sue; Janes, Holly E; Gillespie, Kevin; Seilie, Annette M; Hanron, Amelia E; Rinn, Laurie; Fishbaugher, Matthew; et al.
Abstract: Background: DSM265 is a selective inhibitor of Plasmodium dihydroorotate dehydrogenase that fully protected against controlled human malarial infection (CHMI) by direct venous inoculation of Plasmodium falciparum sporozoites when administered 1 day before challenge and provided partial protection when administered 7 days before challenge. Methods: A double-blinded, randomized, placebo-controlled trial was performed to assess safety, tolerability, pharmacokinetics, and efficacy of 1 oral dose of 400 mg of DSM265 before CHMI. Three cohorts were studied, with DSM265 administered 3 or 7 days before direct venous inoculation of sporozoites or 7 days before 5 bites from infected mosquitoes. Results: DSM265-related adverse events consisted of mild-to-moderate headache and gastrointestinal symptoms. DSM265 concentrations were consistent with pharmacokinetic models (mean area under the curve extrapolated to infinity, 1707 µg*h/mL). Placebo-treated participants became positive by quantitative reverse transcription–polymerase chain reaction (qRT-PCR) and were treated 7–10 days after CHMI. Among DSM265-treated subjects, 2 of 6 in each cohort were sterilely protected. DSM265-treated recipients had longer times to development of parasitemia than placebo-treated participants ( P < .004). Conclusions: This was the first CHMI study of a novel antimalarial compound to compare direct venous inoculation of sporozoites and mosquito bites. Times to qRT-PCR positivity and treatment were comparable for both routes. DSM265 given 3 or 7 days before CHMI was safe and well tolerated but sterilely protected only one third of participants. Abstract : A controlled human malarial infection study was conducted to assess the efficacy of oral DSM265 against preerythrocytic Plasmodium falciparum sporozoite infection. Complete protection was achieved in 33% of volunteers who received DSM265 3 or 7 days before challenge.